Tren Riset Pembangunan Pertanian Berbasis Teknologi Digital Di Indonesia - Raihan Saputra; Annisa Rahmawati; Fakhri Maulana Fauzan; Dewi Rohma Wati (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
The advancement of digital technology has brought about substantial changes within the agricultural sector, particularly in terms of production management, access to information, and decision-making. This study aims to identify research trends related to digital agriculture development in Indonesia in the period 2018–2025 through keyword mapping and analysis of collaboration between authors. The approach used is a Systematic Literature Review (SLR) combined with bibliometric analysis using VOSviewer software. Publication data were analyzed to identify patterns in keyword occurrence, relationships between topics, and the structure of the network of authors contributing to this research. The results of the analysis show that publications on digital agriculture increased rapidly in the period 2023–2025, in line with the increasing need for digital innovation in the agricultural sector. The keywords with the highest dominance include digital technology, agricultural extension, digital marketing, farmer empowerment, digital applications, and artificial intelligence, which describe the direction of research towards technology integration in supporting agricultural efficiency and sustainability. The visualization of the author network shows dense and even collaboration, indicating that research in this field is developing in an integrated and interconnected manner. These findings not only show the development of research trends but can also serve as a basis for formulating more targeted and relevant digitalization strategies and agricultural policies for the digital era, thereby strengthening sustainable national agricultural development.